Semantic Fields in Vulgar Expressions across Cultures: English and Uzbek (KONFERENSIYA, 2025)
This study offers a comparative linguocultural analysis of vulgar and tabooexpressions in English and Uzbek, examining how semantic fields of profanity reflectunderlying cultural values, social norms, and communicative practices. Using corporacompiled from films, television subtitles, social media discourse, and colloquialprogramming, vulgar expressions were categorized into seven semantic domains andanalyzed for frequency and usage patterns. Findings show that English profanity isdominated by sexual and excretory vocabulary, reflecting secular, individualisticcultural orientations and the historical erosion of religious taboos. In contrast, Uzbekvulgarity centers on personal and kinship-based insults, highlighting the importanceof familial honor and collectivist social structures; sexual profanity commonlyappears in mother-insult constructions, and religious profanity is largely avoided.Nonverbal insults likewise exhibit culturally specific patterns, with gestures differingin meaning and offensive intensity across the two cultures. Gendered patterns alsoemerge: Uzbek men employ harsher, dominance-oriented curses, while women tendto use softer or positive “blessing-type” expressions. Overall, the study demonstratesthat profanity functions not merely as linguistic aggression but as a culturallymeaningful system of emotional expression, social regulation, and identityconstruction